Lansia Berdaya, Tekanan Darah Terkendali: Peningkatan Kemampuan Manajemen Diri Pada Penderita Hipertensi - Nurma Afiani; Ira Nurmala; Mahmudah Mahmudah (Jurnal LINK, 2025)
Hypertension is a chronic condition that cannot be cured but can be effectively controlled. Lifelong blood pressure management is essential to prevent the development of cardiovascular complications. Successful hypertension management hinges on the patient’s active participation in the treatment process. The priority issue is the low self-management ability of elderly people with hypertension. Efforts are needed to empower elderly with hypertension. The aim is to improve the self-management ability of elderly people with hypertension. The methods used include lectures, Focus Group Discussion (FGD), practice, and mentoring. Evaluation was carried out with a pre-test and post-test. The sample were elderly people with hypertension who were registered as members of Prolanis, aged 55-65 years, had been diagnosed with hypertension for at least 1 year, and were taking at least one type of antihypertensive medication. The media used was the Self-Management Module. An additional health promotion program was conducted with four sessions in one month for the treatment group. The results showed that the health promotion program was effective in improving self-management skills. Elderly people with hypertension who have good self-management skills will be more compliant with the therapy program, thereby reducing the risk of complications.